2021
DOI: 10.18632/aging.202532
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle-encapsulated microRNA-23a from dorsal root ganglia neurons binds to A20 and promotes inflammatory macrophage polarization following peripheral nerve injury

Abstract: Extracellular vesicles (EVs) are capable of transferring microRNAs (miRNAs or miRs) between two different types of cells and also serve as vehicles for delivery of therapeutic molecules. After peripheral nerve injury, abnormal expression patterns of miRNAs have been observed in dorsal root ganglia (DRG) sensory neurons. We hypothesized that sensory neurons secrete miRs-containing EVs to communicate with macrophages. We demonstrated that miR-23a was upregulated in DRG neurons in spared nerve injury (SNI) mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…51 In particular, enrichment of certain microRNAs in EVs is able to establish a targeted cross-talk in many inflammation-related diseases. Zhang et al 52 reported that sensory neurons transfered EVs-encapsulated miR-23a to promote inflammatory M1 macrophages by binding to A20 and enhance neuropathic pain following the peripheral nerve injury. Interestingly, a recent study manifested that inhibition of miR-10a expression in endothelial cells weakened their anti-inflammatory effects on monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…51 In particular, enrichment of certain microRNAs in EVs is able to establish a targeted cross-talk in many inflammation-related diseases. Zhang et al 52 reported that sensory neurons transfered EVs-encapsulated miR-23a to promote inflammatory M1 macrophages by binding to A20 and enhance neuropathic pain following the peripheral nerve injury. Interestingly, a recent study manifested that inhibition of miR-10a expression in endothelial cells weakened their anti-inflammatory effects on monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study found that microRNA-23a expression is upregulated in DRG neurons after SNI and its subsequent expression in macrophages could promote their polarization towards the pro-inflammatory phenotype by inhibiting A20 and activating the NF-kB signaling. In addition, they demonstrated that the local delivery of miR-23a antagomir via extracellular vesicles (EVs) reduced M1 macrophages and increased M2 macrophages in vivo in mice models [206]. Lastly, miR-223 has an important role in macrophages' polarization since it was found that M2 macrophages and M2 macrophage-derived microvesicles (MVs) are characterized by a significantly higher miR-223 expression compared to the pro-inflammatory phenotype.…”
Section: Gene Therapymentioning
confidence: 99%
“…Similar to miR‐21, DRG sensory neurons secreted miR‐23a‐enriched EVs following nerve injury and were taken up by macrophages to enhance M1 polarization in vitro. A20, an NF‐κB signaling pathway inhibitor, is a verified miR‐23a target gene 102 . Moreover, intrathecally delivering EVs‐miR‐23a antagomir attenuated neuropathic hyperalgesia and reduced M1 macrophages by inhibiting A20 to activate NF‐κB signaling.…”
Section: Studying Mirna Neuropathic Pain Mechanismsmentioning
confidence: 99%
“…Similar to miR-21, DRG sensory neurons secreted miR-23a-enriched EVs following nerve injury and were taken up by macrophages to enhance M1 polarization in vitro. A20, an NF-κB signaling pathway inhibitor, is a verified miR-23a target gene 102. Moreover, intrathecally delivering EVs-miR-23a antagomir attenuated neuropathic hyperalgesia and reduced M1 macrophages by inhibiting A20 to activate NF-κB signaling.5 | S TUDYING lncRNA s AND circRNA s NEUROPATHIC PAIN MECHANIS MS lncRNAs and circRNAs are essential in neuropathic pain development by acting as AS RNA or miRNA sponges, epigenetically regulating pain-related molecules expression, or modulating miRNA processing (Table…”
mentioning
confidence: 99%